2015
DOI: 10.4236/fns.2015.63034
|View full text |Cite
|
Sign up to set email alerts
|

Underweight and Obesity in Low Birth Weight Children in Early Infancy in Japan

Abstract: Introduction: Although there are several reports on the prevalence of underweight or obesity in low birth weight (LBW, <2.5 kg) children, there are few longitudinal studies from birth to early infancy. Methods: We enrolled 177 (93 boys) LBW and 2485 (1267 boys) normal birth weight (NBW, ≥2.5 and <4.0 kg) children. Height and weight data at birth and at 1.5, 3.5, and 5 years were obtained from mother-health child records. Underweight and obesity were defined as <5 th percentile and ≥90 th percentile of the body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…Babies born with lower nutritional levels will need more nutrition at birth to catch up and can cause the body to store more fat reserves, triggering later obesity. This is also in accordance with study conducted by Kato et al 22 which reported that birth weights of less than 2500 g can lead to overweight or obesity. According to Meyre et al 23 the genetic role of modulating insulin can contribute to fetal growth and obesity, and that the genetic role is also involved in obesity in children.…”
Section: History Of Low Birth Weight (<2500 G)supporting
confidence: 93%
“…Babies born with lower nutritional levels will need more nutrition at birth to catch up and can cause the body to store more fat reserves, triggering later obesity. This is also in accordance with study conducted by Kato et al 22 which reported that birth weights of less than 2500 g can lead to overweight or obesity. According to Meyre et al 23 the genetic role of modulating insulin can contribute to fetal growth and obesity, and that the genetic role is also involved in obesity in children.…”
Section: History Of Low Birth Weight (<2500 G)supporting
confidence: 93%
“…There is also a possibility that rates of low birth weight in the past affected the obesity or underweight prevalence in the present. An association between underweight and low birth weight at birth has been shown among children in Japan [44], and lower birth weight was shown to be associated with underweight among children also in China [45]. In addition, one study found that low birth weight was associated with obesity in adults [46], while a meta-analysis showed that low-birth-weight infants have a decreased risk of later overweight [47].…”
Section: Discussionmentioning
confidence: 99%
“…showed that low birth weight children, despite their high rate of growth until the age of 3.5 compared to children with normal birth weight, have a lower BMI and height at the age of 5 than children with normal birth weight. [17]…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the BMI of the participants in the present study, results were similar to the studies of Kato et al . [17] and Darendeliler et al . [18] In these studies, children with low birth weight also had a lower BMI than normal children, which could be due to children's growth rate and nutritional factors.…”
Section: Discussionmentioning
confidence: 99%